Esterification of olive acid oil in supercritical methanol - Akgun, Nalan; Yaprakci, Anil; Candemir, Cansu (WILEY-BLACKWELL, 2010)
The aim of this work was to produce biodiesel from olive acid oil with free fatty acid content of 91.67 wt% by using non-catalytic esterification in supercritical methanol. Design of experiments was used to evaluate the effects of various values of pressure (200-280 bar), temperature (300-380 degrees C), methanol to acid oil volumetric ratio (0.7-1.5), and flow rate (0.4-1.2 mL/min). The optimum process conditions such as temperature of 380 C, pressure of 240 bar, volumetric ratio of acid oil to methanol of 1.12, and flow rate of 0.4 mL/min were obtained using response surface methodology (RSM) coupled with Central Composite Design (CCD). Moreover, it was found that the most effective parameters were temperature and flow rate, which was in good agreement with the experimental value. Furthermore, the fuel properties of biodiesel were upgraded, and then tested following the European standard EN 14214.
Keywords: Acid oil; Biodiesel; Esterification; Response surface methodology; Supercritical methanol; BIODIESEL FUEL; RAPESEED OIL; TRANSESTERIFICATION; KINETICS; Food Science & Technology; Nutrition & Dietetics